(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This study delves into the complex interplay among self-conscious emotion, emotionalregulation, social readjustment, and psychological well-being in women cancer patients. Cancerdiagnoses among women are on the rise, making it crucial to understand the emotional and socialdynamics that influence their psychological well-being. The study employs comprehensive review ofpast literature to explore the multifaceted relationships. Self-conscious emotions, encompassing guilt,shame, pride, and self-image, are examined for their impact on psychological well-being. Emotionalregulation strategies are scrutinized to determine their role in alleviating emotional distress. It exploreshow they adapt to changes in social roles and relationships, focusing on the role of support systems andsocial resources in enhancing psychological well-being. Findings suggest that self-conscious emotionscan significantly affect the psychological well-being of women cancer patients. Emotional regulationskills appear to be essential in managing emotional distress. Furthermore, social readjustment plays apivotal role in determining psychological well-being. This research aims to provide insights into theexperiences of women cancer patients, shedding light on their emotional and social challenges. Itemphasizes the need for tailored support and interventions to improve psychological well-being.Ultimately, the study contributes to a more comprehensive approach to cancer care, addressing theholistic needs of women facing this formidable disease.